Lung tumor discovered during the pre-employment medical check-up of a candidate for work abroad - case report - Vešović, Dušan; Mihajlović, Nina; Ilic Todoric, Lana; Karlicic, Vukoica; Petrovic, Dalibor; Banovic, Svetlana; Vojinovic, Milos; Radojicic, Bojan; Milanov, Marko; Culafic Zuber, Andrijana (PONS - medicinski časopis, 2025)
AbstractIntroduction. Lung cancer is one of the most common and deadliest forms of cancer with a high mortality rate. Regular health check-ups play a crucial role in the early detection of malignant diseases, especially among employed individuals. Aim. The aim of the paper is to present a case of a diagnosed lung tumor in a person who underwent pre-employment medical check-up in order to obtain a work visa for the purpose of employment abroad.Case report. This paper presents the case of a 47-year-old architect who was diagnosed with a lung tumor during a preventive medical check-up for obtaining a work visa. The patient was a smoker without any health complaints. A chest X-ray revealed a well-defined shadow in the left lung field. Further diagnostic procedures (CT scan and bronchoscopy) confirmed the presence of a carcinoid (NET GR1). The tumor was successfully removed through surgery, and the patient received a positive opinion on work capability after a short rehabilitation period.Conclusion. This case highlights the importance of preventive medical examinations that enable early detection and timely intervention, significantly improving the chances of successful treatment. Early detection of malignant diseases reduces the need for invasive treatments, lowers treatment costs, and improves patients' quality of life. However, challenges include false positive and negative results, which can lead to unnecessary interventions or false security. The role of occupational medicine is crucial in early detection, providing a unique opportunity to identify malignant diseases through regular check-ups. A multidisciplinary approach, including collaboration among oncologists, surgeons, radiologists, and pulmonologists, is essential for optimal planning and execution of treatment, contributing to the best possible outcomes for patients. In conclusion, this paper emphasizes the need for continuous educational programs and raising awareness about the importance of early lung cancer detection. Public education and the implementation of preventive health programs can significantly reduce lung cancer mortality. This case serves as a reminder for all healthcare professionals about the importance of a careful and thorough approach to each patient, because every medical check-up can be an opportunity to save a life. Key words: tumor of the lungs, carcinoid, preventive medical check-up, occupational medicine
Keywords: tumor pluća, karcinoidni tumor, preventivni zdravstveni pregledi, medicina rada